An Empirical Study of Visitors' Experience at Kuching Orchid Garden with Mobile Guide Application. (3rd June 2018) - Othman, Mohd Kamal; Idris, Khairul Izham; Aman, Shaziti; Talwar, Prashanth
Abstract : This empirical study was conducted to measure visitors' experiences with a mobile guide application at Kuching Orchid Garden (KOG). A between-group experimental design with 114 participants was conducted to test three groups;( 1 ) a group using the mobile guide application as an information aid, ( 2 ) a control group (with no information aid), and( 3 ) a group using pamphlets to explore the KOG. The Museum Experience Scale (MES) was used to evaluate visitors' experience for all participants, whilst the Multimedia Guide Scale (MMGS) was used to evaluate the visitors' experience with the mobile guide group. The most notable result from the Museum Experience Scale (MES) showed an impact on the visitors in terms of knowledge and learning when using the mobile guide application. However, the study found that enhancing visitors experience goes beyond simply providing interactive technologies in public settings to aid with information delivery. A limitation was providing relevant information in a timely and seamless manner due to inaccuracies of mapping between physical and digital environments. Future works should consider beacons and other Bluetooth low energy (BLE) technology to address the issues with location based devices. It is also important to highlight that the use of one's own device had a significant impact on learnability and control of the device, thus suggesting that the BYOD concept should be widely used in informal educational settings implementing mobile guide applications. The use of MES and MMGS informs future researches with an understanding of the different dimensions of visitors' experiences with mobile guide technology in public spaces to inform mobile application development that may further boost visitors' engagement, emotional connection, and meaningful experience.